RELIABILITY ANALYSIS OF AIRCRAFT FLEET IN NIGERIA - Chioma, Okoro Onyedikachi (Proceedings of National Aviation University (archive), 2019)
This article is devoted to the reliability analysis of aircraft in Nigeria as well as their systems and structures during operation. This is necessary for the development of methods for diagnosing technical conditions and the optimization of aircraft maintenance programs. The results of this study identify factors affecting flight safety in terms of reliability parameters which are presented in this article.